ANALISIS BANTUAN BANK INDONESIA PADA PROGRAM KEWIRAUSAHAAN GENERASI BARU INDONESIA (GENBI) KALIMANTAN BARAT - Lulu, Lorensia; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is entitled Analysis of Bank Indonesia Assistance in the West Kalimantan Indonesian New Generation Entrepreneurship Program. A common problem in this study is How Bank Indonesia Assists the West Kalimantan Indonesian New Generation Entrepreneurship Program (GenBI). This study aims to determine the form of Bank Indonesia's assistance to the Indonesian New Generation (GenBI) entrepreneurship program in West Kalimantan. The research method used is descriptive with a qualitative research approach. Data collection is done by observation, interviews, and documentation. Data sources used are primary and secondary data sources. Data processing and analysis techniques through three stages, namely; data reduction, data presentation and conclusion drawing. The results of this study indicate that; (1) Bank Indonesia Assistance to the West Kalimantan Indonesian New Generation Entrepreneurship Program (GenBI), hydroponic plants and catfish farming. (2) The implementation of entrepreneurship itself from the New Indonesian Generation (GenBI) of West Kalimantan after the assistance of Bank Indonesia, (3) The benefits felt by Indonesian New Generation (GenBI) entrepreneurship in West Kalimantan.Keywords: Entrepreneurship, Bank Indonesia, Indonesian New Generation (GenBI).AbstractThis thesis is entitled Analysis of Bank Indonesia Assistance in the West Kalimantan Indonesian New Generation Entrepreneurship Program. A common problem in this study is How Bank Indonesia Assists the West Kalimantan Indonesian New Generation Entrepreneurship Program (GenBI). This study aims to determine the form of Bank Indonesia's assistance to the Indonesian New Generation (GenBI) entrepreneurship program in West Kalimantan. The research method used is descriptive with a qualitative research approach. Data collection is done by observation, interviews, and documentation. Data sources used are primary and secondary data sources. Data processing and analysis techniques through three stages, namely; data reduction, data presentation and conclusion drawing. The results of this study indicate that; (1) Bank Indonesia Assistance to the West Kalimantan Indonesian New Generation Entrepreneurship Program (GenBI), hydroponic plants and catfish farming. (2) The implementation of entrepreneurship itself from the New Indonesian Generation (GenBI) of West Kalimantan after the assistance of Bank Indonesia, (3) The benefits felt by Indonesian New Generation (GenBI) entrepreneurship in West Kalimantan.Keywords: Entrepreneurship, Bank Indonesia, Indonesian New Generation (GenBI).